Synthesis, investigation of the structure and physico-chemical properties of modified solid-phase extractants (SPE) based on N,N,N’,N’-tetraoctyldiglycolamide (TODGA) - Aleksandr A. Savelev; Valeriy I. Rachkov (Nuclear Energy and Technology)
The paper presents the results of the development of modified solid-phase extractants (SPE) based on N,N,N’,N’-tetraoctyl diglycolamide (TODGA) intended for the selective extraction of americium-241 from nitric acid solutions of liquid radioactive waste. (LRW). The structural and physico-chemical properties of synthesized materials, including granulometric composition, porosity, and stability in nitric acid media, have been studied. The developed SPEs are stable in nitric acid solutions and meet the size requirements for use in industrial sorption columns. The results obtained can be used as a basis for creating technological schemes for the processing of LRW based on synthesized experimental modified samples of SPE TODGA, in particular for the isolation of minor actinides, including americium-241.